2016
DOI: 10.1101/gad.281162.116
|View full text |Cite
|
Sign up to set email alerts
|

Female mice lacking Xist RNA show partial dosage compensation and survive to term

Abstract: X-chromosome inactivation (XCI) compensates for differences in X-chromosome number between male and female mammals. XCI is orchestrated by Xist RNA, whose expression in early development leads to transcriptional silencing of one X chromosome in the female. Knockout studies have established a requirement for Xist with inviability of female embryos that inherit an Xist deletion from the father. Here, we report that female mice lacking Xist RNA can, surprisingly, develop and survive to term. Xist-null females are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 66 publications
3
64
3
Order By: Relevance
“…In female mammals, X-to-autosome dosage compensation is achieved by X-chromosome inactivation and current evidence indicates that this process is essential for female embryonic development and adult homeostasis (Schulz and Heard, 2013; Yang et al, 2016). The prevailing model therefore suggests that human primed female ESCs and iPSCs undergo XCI during differentiation, but the literature on the state of the X in undifferentiated PSCs and upon differentiation has remained controversial (Anguera et al, 2012; Barakat et al, 2015; Hall et al, 2008; Hoffman et al, 2005; Kim et al, 2014; Lengner et al, 2010; Mekhoubad et al, 2012; Nazor et al, 2012; Pomp et al, 2011; Shen et al, 2008; Silva et al, 2008; Tchieu et al, 2010; Tomoda et al, 2012; Vallot et al, 2015; Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In female mammals, X-to-autosome dosage compensation is achieved by X-chromosome inactivation and current evidence indicates that this process is essential for female embryonic development and adult homeostasis (Schulz and Heard, 2013; Yang et al, 2016). The prevailing model therefore suggests that human primed female ESCs and iPSCs undergo XCI during differentiation, but the literature on the state of the X in undifferentiated PSCs and upon differentiation has remained controversial (Anguera et al, 2012; Barakat et al, 2015; Hall et al, 2008; Hoffman et al, 2005; Kim et al, 2014; Lengner et al, 2010; Mekhoubad et al, 2012; Nazor et al, 2012; Pomp et al, 2011; Shen et al, 2008; Silva et al, 2008; Tchieu et al, 2010; Tomoda et al, 2012; Vallot et al, 2015; Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The silencing of the X-chromosome is accompanied by heterochromatin formation and stably maintained throughout the lifetime of the organism (Augui et al, 2011; Disteche, 2012). Genetic approaches have indicated that XCI is necessary for development and adult homeostasis (Schulz and Heard, 2013; Yang et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It is likely that a strategy that effectively reactivates MeCP2 will, at least to some extent, reactivate other loci on the Xi. Even though undesirable side effects resulting from such a nonselective reactivation of the Xi might hinder use of MeCP2 reactivation for therapeutic purposes, a recent study demonstrating grossly normal organogenesis of XIST-deficient female mice suggests that partial deficiency in dosage compensation is surprisingly well tolerated and compatible with both cellular and organismal viability (22,47).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and faithful XCI is critical to development, as persistence of two active X chromosomes results in a dosage imbalance that compromises development (Takagi and Abe, 1990; Schulz et al, 2014; Yang et al, 2016). Because XCI occurs synchronously in ~20 cells of the epiblast, we hypothesize that intercellular communication between the epiblast and surrounding extraembryonic cells may help coordinate the timing of this process, most likely through a signal transduction pathway.…”
Section: Introductionmentioning
confidence: 99%